Characterisation of intra-tumoural genetic heterogeneity in Wilms tumours. (24th May 2012) - Apps, JR; Chagtai, T; Popov, S; Pearce, K; Olsen, O; Rampling, D; Sebire, N; Williams, R; Pritchard-Jones, K
Abstract : Introduction: Biomarkers are increasingly used to support risk stratification and clinical decisions in Paediatric Oncology. Implicit in the clonal evolutionary theory of cancer development is the evolution of cells derived from an initiating clone through natural selection acting upon intra-tumoural genetic heterogeneity. Wilms tumours frequently present as large macroscopically heterogeneous masses, and can be multifocal in origin. Several studies have indicated the presence of intra-tumoural genetic heterogeneity in a range of tumours. This study aimed to characterise intra-tumoural genetic heterogeneity within Wilms tumours. Methods: Multiple snap frozen samples were taken from consecutive post chemotherapy Wilms tumour nephrectomy specimens at Great Ormond Street Hospital, May-October 2011. DNA was extracted from frozen specimens and analysed using the Illumina CytoSNP array for copy number variation. Results: 23 samples were analysed from 10 separate tumours. 2 cases showed clear heterogeneity between samples. In one case gains of chromosome 8 and 13 were conserved across two tumour samples however gains of chromosomes 2 and 12 were present in one sample and of chromosome 7 in the other. In a separate case partial gain of 22q was present in both samples and 1q and partial 1p gain in only one sample. A third case showed localised heterogeneity with loss of 7p and gain of 7q present in two samples whilst gain of chromosome 8 was more apparent in only one sample. In three other cases, the changes observed were conserved between two or more samples (gain of 12, 13 and 20 in one case, gain of 12 in the second, and partial 9q21-22 deletions in the third). 4 tumours had no apparent copy number changes. Discussion: 6 of 10 tumours showed copy number variation. In all of these cases certain copy number variations were conserved between multiple samples of an individual tumour, consistent with a clonal origin. In three cases there was intra-tumoural genetic heterogeneity. Further understanding such heterogeneity may aid in deciphering the genetic changes in the evolution of Wilms tumours and help identify driver mutations. In addition, as the use of biomarkers, such as 1q gain, enters clinical practice understanding such heterogeneity will be important for establishing appropriate sampling strategies.